2014
DOI: 10.3311/ppch.7301
|View full text |Cite
|
Sign up to set email alerts
|

The role of dissolution testing in quality control

Abstract: Semisolid systems (creams, gels etc.) for dermal application get more and more importance in pharmaceutical and cosmetic industry. However the number of methodologies for their physico-chemical characterization have been increasing; development of methods for the measurement of the active agent's release onto the skin surface is still a challenging task. Beside measuring the amount of the active agent reaching the skin; dissolution testing (also called release testing) can be also a good indicator of product c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Different mathematical models such as zero-order, firstorder, Korsmeyer-Peppas, Hixson-Crowell, and Higuchi models were used to study the drug release kinetics. This study showed that the gel dissolution data is best fitted to the Higuchi equation for all four formulations [Table 4], which describes the quantity of drug release from a semi-solid is a linear function of the square root of time [49]. The Higuchi model had the highest correlation coefficient-r 2 (0.9958-0.9980).…”
Section: In-vitro Drug Releasementioning
confidence: 96%
See 1 more Smart Citation
“…Different mathematical models such as zero-order, firstorder, Korsmeyer-Peppas, Hixson-Crowell, and Higuchi models were used to study the drug release kinetics. This study showed that the gel dissolution data is best fitted to the Higuchi equation for all four formulations [Table 4], which describes the quantity of drug release from a semi-solid is a linear function of the square root of time [49]. The Higuchi model had the highest correlation coefficient-r 2 (0.9958-0.9980).…”
Section: In-vitro Drug Releasementioning
confidence: 96%
“…Dissolution testing is being used to measure the quantity of active pharmaceutical ingredients bioavailable in the skin. It can also be employed as a quality control procedure because a dissolution test can reveal changes in a product's composition [49]. The nanoparticle release profile of the four formulations was compared with each other.…”
Section: In-vitro Drug Releasementioning
confidence: 99%
“…It could also allow selection of the active substances in the external phase for immediate action and that in the internal aqueous phase for prolonged release. The reduction of irritation caused by some of the active substances is also possible due to their controlled release [7][8][9][10][11][12].…”
mentioning
confidence: 99%